Evidence gap map on impacts of Socio-Technical Innovation Bundles (STIBs) on women’s empowerment and resilience. CGIAR Initiative on Gender Equality (HER+) - Pasha, Atika; Khan, Sarah; Urueña, Viviana; Huonen, Ruthus; Furlani, Irene; Delgerchuluun, Ankhbayar; Puskur, Ranjitha; Mishra, Avni; Mukhopadhyay, Prama; Gartaula, Hom Nath; Nchanji, Eileen; Ketema, Dessalegn Molla; et al. (2023)
A combination of factors, including policies, technological advancements in response to climate change and social needs, and changes in market demand, have triggered considerable agricultural transformations in recent decades (Timmer, 1988; Viswanathan et al., 2012; Thanh et al., 2021). Yet, technological innovations alone do not necessarily make agricultural transformations sustainable and inclusive over time. Several actors are now focusing on introducing bundled interventions combining technical and/or technological innovations with social innovations. Their aim is to apply a multi-pronged approach to agricultural transformation that simultaneously allows technological advancements, with increased adoption of new methods and tools, and alleviates barriers in access to inputs and credits. Gwynne and Ortiz (1997) provide a clear example from Chile, proving how institutional changes in land ownership, expansion of productive investments, and provision of financial inputs to farmers succeeded in promoting agricultural development, especially increasing agricultural output and labour productivity, among others. Also, Joshi and Joshi (2019) reckon the importance of policies in Nepal and their significance in combination with technology adoption to avoid negative impacts on food production and access and availability of water and energy. Although these bundled interventions target all farmers in principle, women farmers are often disadvantaged, as the bundle configuration does not consider their preferences, capacities and/or capabilities. This “fits all” approach is particularly problematic as women constitute about half of the agricultural labour force, and if they face greater difficulties in accessing these bundles, and reaping the benefits derived from them, then these bundles fail to empower half of the target population. With the intention to bridge the existing gender gaps, the socio-technical innovation bundles or STIBs need to be gender-responsive and align with women’s preferences, attitudes, and capacities. In order to understand which configurations of STIBs can be most beneficial for women, existing evidence related to STIB interventions and their impact on women’s resilience and empowerment needs to be examined. Therefore, this evidence gap map reviews the existing literature on the effect of different STIBs and provides evidence on how and whether these bundles empower women and enhance their resilience. This evidence gap map will guide and inform decision-making about the design and implementation of STIBs in different contexts and how enabling factors can improve or modify their performance